2018
DOI: 10.1212/cpj.0000000000000526
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus encephalitis radiographically mimicking lateral medullary stroke

Abstract: Cytomegalovirus (CMV) is a double-stranded DNA virus from the herpes virus family. Disseminated or focal end-organ disease typically occurs in immunocompromised individuals, often in the setting of advanced HIV or organ transplantation. Neurologic manifestations include focal encephalitis, meningitis, ventriculoencephalitis, and polyradiculitis. After the advent of highly active antiretroviral therapy (HAART), the incidence of CMV disease has decreased by as much as 80%. 1 This decrease largely predates the wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Anderson et al [7] reported typical MRI of AIDS-associated CMV encephalitis revealed equal to slightly low signal on T1WI, low signal on T1WI, high signal on T2WI and FLAIR, slightly high signal on DWI, and low signal on ADC. Restricted diffusion MRI lesions is one of the speci c manifestations of CMV encephalitis [8,9] and may exist for a long time [10] . Only a few of them have been reported to have enhanced contrast.…”
Section: Discussionmentioning
confidence: 99%
“…Anderson et al [7] reported typical MRI of AIDS-associated CMV encephalitis revealed equal to slightly low signal on T1WI, low signal on T1WI, high signal on T2WI and FLAIR, slightly high signal on DWI, and low signal on ADC. Restricted diffusion MRI lesions is one of the speci c manifestations of CMV encephalitis [8,9] and may exist for a long time [10] . Only a few of them have been reported to have enhanced contrast.…”
Section: Discussionmentioning
confidence: 99%